Efficacy and safety of imatinib mesylate in systemic sclerosis. A systematic review and meta-analysis. (1st September 2020) - Liakouli, Vasiliki; Ciaffi, Jacopo; Ursini, Francesco; Ruscitti, Piero; Meliconi, Riccardo; Ciccia, Francesco; Cipriani, Paola; Giacomelli, Roberto
ABSTRACT: Objectives: To synthetize the available evidence concerning efficacy and safety of imatinib mesylate, a tyrosine kinase inhibitor, in systemic sclerosis (SSc). Methods: A systematic search following the PRISMA-statement in PubMed/MEDLINE, Cochrane CENTRAL, and Web of Science databases up to 7 February 2020 was conducted. Considering the substantial heterogeneity expected, a random-effects model to pool data from selected studies was adopted. Results: After a treatment period ranging from 6 to 12 months, the pooled analysis revealed that imatinib mesylate significantly improved modified Rodnan skin score (mRSS) (mean difference [MD] = −3.091, 95%CI −6.081 to −0.102, p = 0.043), whereas health-related assessment questionnaire (HAQ) remains unchanged (−0.096; 95 CI −0.197 to −0.006). Data regarding change in pulmonary function tests were insufficiently consistent to be considered eligible for meta-analysis. Finally, regarding safety, the authors found a pooled dropout rate due to all adverse events of 22% and a rate of serious adverse events of 17%. Conclusion: The significant change within the range of clinical relevance of mRSS suggests the possible use of imatinib mesylate in SSc, whereas it is still not possible to draw firm conclusions regarding the efficacy of the drug on lung involvement. Specifically designed and powered studies are needed to investigate imatinib mesylate therapy in SSc.